Inflation and counter-inflationary policy measures: The case of Spain - Jorge Uxó González (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
Like in other European countries, several supply shocks (bottlenecks related to the end of the pandemic, tensions in international gas and oil prices, and war in Ukraine) have led to a rise in the inflation rate in Spain since March 2021. This has been amplified by the functioning of energy markets, especially electricity, and price increases have spread progressively to other sectors. As a result, the forecast average inflation in 2022 is 8.5%, similar to the Eurozone average. Until August 2022, Spain had a year-on-year inflation rate above this average, but the trend has changed: in October, inflation fell by 3.4 pp in Spain, while it had risen by 1.6 pp in the monetary union. Spain was the economy with the second lowest inflation. The authorities have adopted significant measures to reduce inflation, especially in energy (capping gas in the electricity market, limiting the gas price for consumers in the regulated tariff, lowering indirect taxes, or discounts for vulnerable households) and public transport and housing rents. Other measures include transfers to the most affected households and economic sectors to offset the effects of inflation. Despite this, weak nominal wage growth and the pass-through by firms of higher costs to their prices (maintaining or increasing profit margins) are leading to an unequal distribution of the effects of inflation, which wage earners mainly bear. Changing this situation should be the focus of economic policy from now on.
urn:nbn:de:101:1-2023011910541863231555
Keywords: 330; Austrian Chamber of Labour Vienna (AK Wien); Inflation; Spain; gas; electricity; price cap; HICP; energy; distribution; social pact; real wages